A Review of the Nature and Development of Lying and Deception and Considerations for Teaching Prosocial Lying to Autistic Persons - Hutchins, Tiffany L. (Seminars in Speech and Language, 2022)
Compared with their neurotypical (NT) counterparts, persons with autism appear to be less inclined to tell lies and less skilled in delivering sophisticated forms of deception. At the same time, some forms of deception like white lies and prosocial lies are frequent in human interaction because they are important for social success. This article challenges the reader to evaluate the therapeutic potential for prosocial deception and teaching white-lie telling to autistic persons. The nature and development of antisocial and prosocial lying in NT development and autism are reviewed. Considerations for when to (and when not to) teach the skill of empathic lying are discussed and recommendations for how to teach the comprehension and production of prosocial lies are offered.
Keywords: lying; deception; autism; teaching; prosocial lying